ABOUT THE NOTION OF WORD (Muitas Vozes, 2021)
This text discusses the indeterminacy of the notion of word, showing that the unsuccessful attempts to define it - by orthographic, phonological, morphosyntactic or semantic criteria - end up defining distinct and incompatible theoretical objects. To the extent that the notion of word is central to theories of language and that without a clear notion of word it is not possible to distinguish morphology from syntax, two alternatives are presented: either we clearly define what a word is, or we abandon this notion in favor of some other.